2008
DOI: 10.1111/j.1751-7176.2008.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Anger Types: Heritability and Relation to Blood Pressure, Body Mass Index, and Left Ventricular Mass

Abstract: The relationship between anger and cardiovascular morbidity has not been investigated among Mexican Americans. This exploratory study examined the heritability of anger types and their relationship to cardiovascular variables in samples of unrelated and related Mexican Americans residing near Chicago, Illinois. All of the anger variables of the Spielberger Anger Expression Scale (in, out, control, total expression) had significant heritabilities. Using the total sample of related individuals, higher female ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, the relationship between anger-control and glucose metabolism did not depend on body fat distribution: low anger-control was associated with higher fasting glucose regardless of BMI and WHR. While anger has been associated with adiposity (Gleiberman, Greenwood, Luke, Delgado, & Weder, 2008; Midei, Matthews, & Bromberger, 2010), our study is the first to document a synergistic relationship of anger and adiposity on glucoregulation in nondiabetic individuals, showing that anger-in and anger-out amplify the adverse relationships between adiposity and glucoregulation.…”
Section: Discussionmentioning
confidence: 53%
“…However, the relationship between anger-control and glucose metabolism did not depend on body fat distribution: low anger-control was associated with higher fasting glucose regardless of BMI and WHR. While anger has been associated with adiposity (Gleiberman, Greenwood, Luke, Delgado, & Weder, 2008; Midei, Matthews, & Bromberger, 2010), our study is the first to document a synergistic relationship of anger and adiposity on glucoregulation in nondiabetic individuals, showing that anger-in and anger-out amplify the adverse relationships between adiposity and glucoregulation.…”
Section: Discussionmentioning
confidence: 53%
“…Controversial evidence on the correlation between anger and BP currently exists. 16 While some authors have found anger suppression coping style to induce BP elevation, other authors found anger expression to heighten cardiovascular activation. 7 These controversies can be attributed to variations in concepts or measurements that lead to inconsistent results.…”
Section: How Far Does Anger Contribute To Initiating Essential Hypertmentioning
confidence: 99%
“…A few studies examining relationships between anger, hostility and CVD outcomes have reported stronger effects among non-Latino blacks when compared with non-Latino whites (Magai et al, 2003; Markovitz et al, 1997; Tindle et al, 2009; Williams et al, 2007). To our knowledge only one study has evaluated anger and hostility as CVD risk factors among Latinos, and found that the dimension of “anger-out” was related to left ventricular mass, but only in females (Gleiberman et al, 2008). Consequently, additional work evaluating how these psychosocial factors and their dimensions relate to CVD risk in Latino women is greatly needed.…”
mentioning
confidence: 99%